2021
DOI: 10.7224/1537-2073.2021-005
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Support of a Behavioral Intervention for Trait Conscientiousness in Multiple Sclerosis

Abstract: Background: Conscientiousness, or the proclivity for deliberation, achievement, and order, declines in many people with multiple sclerosis (MS). Decreased Conscientiousness predicts future cognitive deterioration, brain atrophy, and employment loss in people with MS. As a psychological trait, it may be an actionable antecedent to these important outcomes. We pilot tested an application (app)-facilitated behavioral intervention to help adaptation to low Conscientiousness and, in turn, improve employment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this specific context, Fuchs et al employed a technology-aided approach, integrating in-person psychotherapy, telehealth psychotherapy, and a smartphone application designed as an external aid, specifically targeting pwMS with low conscientiousness. They found that pwMS who underwent this treatment experienced better work outcomes over three months compared to those without treatment [ 52 ]. Therefore, these interventions would be beneficial in assisting pwMS in effectively managing the challenges and limitations associated with their condition.…”
Section: Discussionmentioning
confidence: 99%
“…In this specific context, Fuchs et al employed a technology-aided approach, integrating in-person psychotherapy, telehealth psychotherapy, and a smartphone application designed as an external aid, specifically targeting pwMS with low conscientiousness. They found that pwMS who underwent this treatment experienced better work outcomes over three months compared to those without treatment [ 52 ]. Therefore, these interventions would be beneficial in assisting pwMS in effectively managing the challenges and limitations associated with their condition.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot interventional trial, 11 pwMS with low baseline conscientiousness were randomized into 12-week-long behavioral treatment that utilized the motivational framework of expectancy value theory. ( Fuchs et al, 2021 ) Structured phone application helped patients identify personal values and goals, and how certain behaviors could help accomplish these goals. All patients reported benefits from the intervention and the treatment group had significantly more positive employment outcomes.…”
Section: Discussionmentioning
confidence: 99%